Antifosfatidylserinové protilátky u zen s poruchami reprodukce - Fialová, L; Mikulíková, L; Benesová, O; Zwinger, A; Hájek, Z; Malbohan, I (Ceska gynekologie, 1996)
Antiphosphatidylserine antibodies (APSA) belong to the heterogeneous population of antiphospholipid antibodies (APA) which are oriented above all against negatively charged phospholipids. The presence of APA in women is closely associated with repeated miscarriages and other complications during pregnancy. The most frequently detected specific antibodies in these patients are autoantibodies against cardiolipin and phosphatidylserine (PS). In a group of 84 pregnant women where within the framework of biochemical prenatal screening of inborn developmental defects serum levels of alpha-1-fetoprotein, choriogonadotropin and trophoblast specific beta-1-glycoprotein were examined as well as in 22 women treated for primary sterility and 22 blood donors the authors assessed, using the ELISA method, antiphosphatidylserine and cardiolipin antibodies (ACA). They found an increased prevalence of APSA in all examined groups as compared with the control group of blood donors. In pregnant women the prevalence of APSA and ACA did not differ and at least one type of antibodies was detected in 20.1%. In pregnant women with positive APSA in the case-records spontaneous abortions were recorded, or imminent abortions during the present gestation or treatment on account of sterility, and in some instances also changes of foetoplacental antigen serum levels were found. It is therefore likely that the presence of APA in women may be one of the factors participating in reproductive disorders and that assessment of APSA together with APA may extend the spectrum of immunological examinations, in particular in sterile and infertile women.
Keywords: dospělí; těhotenství; antifosfolipidové protilátky; Humans; Infertility, Female; těhotenství - specifické beta-1-glykoproteiny; alpha-Fetoproteins; Phosphatidylserines; ženská infertilita; Pregnancy-Specific beta 1-Glycoproteins; Antibodies, Anticardiolipin; Adult; Chorionic Gonadotropin; alfa-fetoproteiny; antikardiolipinové protilátky; ženské pohlaví; fosfatidylseriny; lidé; Antibodies, Antiphospholipid; choriogonadotropin; Pregnancy; Female